The good and bad news about glutamate in drug addiction. (November 2016) - Spencer, Sade; Scofield, Michael; Kalivas, Peter W
In 1998 we published a perspective review describing how drug-induced neuroadaptations might serve towards understanding drug craving. We proposed experimental perspectives to help discern data relevant to long-lasting brain changes, and to distinguish dopamine-related changes that were largely pharmacological from glutamatergic changes that were based on drug–environment associations. These perspectives are embedded in drug abuse research, and the last 18 years has witnessed marked development in understanding addiction-associated corticostriatal glutamate plasticity. Here we propose three new perspectives on how the field might approach integrating and using the emerging data on glutamatergic adaptations. (1) Consider adaptations produced in kind across drug classes as most useful towards understanding shared characteristics of addiction, such as relapse. (2) Consider how drug-induced changes in glia and the extracellular matrix may contribute to synaptic alterations. (3) Make measurements not only at late withdrawal, but also during drug seeking events to capture transient changes that mediate active drug seeking that are shared across drug classes.